The autocratic military dictatorship Benavides and instrumentalized electoral period of 1939 - Molinari Morales, Tirso Anibal (2011)
This is an approach to the political situation during the elections carried out in 1939 under Oscar R. Benavides dictatorial conditions. The dictator tried to find out an official exit to the crisis of his military regime. At the end, he got the continuity of such officialist exit by using in a fraudulent way to the business man Manuel Prado.